Political parties versus presidents. An analysis of ideological congruence in Latin America - Otero Felipe, Patricia; Mateos, Araceli; Rivas, Cristina (Revista Latinoamericana de Opinión Pública, 2020)
This study aims the political congruence in Latin American presidentialist democracies. It analyzes the levels of ideological congruence between parties and presidential candidates with their voters. The data used come from Americas Barometer at Vanderbilt University and Latin American Elites Project at the University of Salamanca for 11 Latin American countries between 2004 and 2014. The results conclude that the ideological links in Latin America are varied. Voters tend to be more congruent with the political parties they vote for in the legislative than with the candidates they vote for president, reinforcing the idea of dual legitimacy and dual representation in these countries. The radicalism, and the number, of parties and candidates appears as the most significant variables to explain ideological congruence.